Echoes of Historicity in Bhim Birag’s Sworsamratako Samjhana - Shrestha, Tara Lal (International Research Journal of MMC, 2022)
A piece of art or a literary piece is an important source of politico-cultural context where/when an artist or author exists. One of the instances is Bhim Birag’s memoir Sworsamratako Samjhana (The Reminiscence of the Vocal King of Nepal). This paper firstly discusses how Bhim Birag turned to be an artist, shifting from Birgunj to Hetauda, and how not only the place and people associated with him determined his personality but power within a politico-cultural atmosphere also shaped his personal association and artistic activities. It primarily discusses the contexts associated to the text Sworsamratako Samjhana with reference to the information gathered through personal interviews, group discussions and interactions along with published documents. Secondly, it presents instances of friendship between Bhim Birag and Narayan Gopal, which began from Birgunj, nurtured in Hetauda and continued till the end of their life that altered not only their future but also shaped the history of modern Nepali music within the Panchayat period. Finally, the paper attempts to analyse the instances about the association between them and the influence of the politico-cultural context in their biographies and creations.